Heteronymic Translation Project: The Translator as Experimenter in Fernando Pessoa’s “Lisbon. What the Tourist Should See” - Mijas, Hanna (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2024)
This article examines the translation of Fernando Pessoa’s guidebook, focusing on the translator’s innovative approach that transcends traditional fidelity to the source text. By employing a heteronymic method inspired by Pessoa’s literary technique of creating multiple, distinct personas, the translator re-imagines the original work, introducing new layers and perspectives. The translation transforms the guidebook from a simple reproduction into a dynamic narrative in which Lisbon itself becomes a heteronym—an active participant who speaks about Pessoa rather than merely being described by him. This article explores the implications of this creative translation, emphasizing the interplay between the visibility of the translator and the production of new meanings within the text, and demonstrates how the introduction of additional textual elements enriches the original narrative, offering readers a fresh, interactive engagement with both the city of Lisbon and Pessoa’s literary world.